Insight on the Characterization of MoS2 Based Devices and Requirements for Logic Device Integration. (1st January 2016) - de la Rosa, César J. Lockhart; Arutchelvan, Goutham; Radu, Iuliana; Lin, Dennis; Huyghebaert, Cedric; Heyns, Marc; De Gendt, Stefan
Abstract : MoS2 based transistors are being explored as a promising candidate for different applications. The techniques employed to characterize these devices have been directly adapted from 3D semiconductors, without considering the validity of the assumptions. In this work, we discuss the limitations of two-probe (2P), four probe (4P) and transfer length methods (TLM) for extracting electrical parameters. Based on finite-element modeling, we provide design considerations for 4P structures to measure more accurately. Extracting the parameters from these techniques in the appropriate regimes, we identify contact resistance R C to be critical for scaled MoS2 devices. Using 4P and TLM measurements along with temperature dependent measurements, we derive further insights into the behavior of the R C in the subthreshold and linear regime. Additionally, we propose an empirical model for the on-state contact resistance.